Content Feasibility and 21st-Century Skill Support in Grade XII Geography Textbooks under Indonesia’s Merdeka Curriculum: A Content Analysis - Anita Liliana; Bayu Wijayanto; Dedi Hermon (AL-ISHLAH: Jurnal Pendidikan, 2025)
Textbooks play a vital role in supporting learning and instructional delivery, particularly under Indonesia’s Merdeka Curriculum, which emphasizes not only academic standards but also the development of 21st-century competencies. This study evaluates the feasibility of Grade XII Geography (Phase F) textbooks and their integration of Problem-Based Learning (PBL), Project-Based Learning (PJBL), and 4C skills—critical thinking, creativity, communication, and collaboration. A quantitative content analysis was conducted on three widely used textbooks, selected purposively from senior high schools in Jambi City. The evaluation used a rubric based on national curriculum standards (BSKAP), textbook assessment frameworks, and 4C competency indicators. Each textbook was scored across five content feasibility standards, PBL/PJBL integration, and 4C skill representation. All textbooks demonstrated high feasibility, averaging 93% across content quality indicators. Book C exhibited the most comprehensive integration of PBL, PJBL, and 4C skills, offering diverse activities and assessment formats. Book A was strongest in fostering critical thinking, while Book B emphasized communication and collaboration. However, inconsistencies were noted in environmental engagement, digital resource use, and visual quality, particularly in Book B. While the textbooks align with curriculum objectives, refinements are needed to fully support innovative, student-centered learning. Recommendations include incorporating authentic environmental tasks, enhancing digital interactivity, and expanding project diversity. The study is limited by regional scope and rubric subjectivity; future research should include Grades X and XI and investigate links to student learning outcomes.